Implementasi Data Akuntansi Keuangan pada Abang Bengkel Motor Menggunakan Zahir Accounting - Siti Faizah; Amalia Mayfriani Putri (Artikel Ilmiah Sistem Informasi Akuntansi, 2022)
Abstract - Abang Motorcycle Workshop is a business that is engaged in the automotive sector, by offering services and installations to overcome difficulties in motorcycle spare parts by buying these needs from Abang Motor Workshop. This workshop requires a computerized system to make it easier to make financial reports. The financial recording system in this workshop still uses a manual method, so that in the recording there are still frequent errors, ranging from financial transactions, storing data on stock items and those related to the sales process and report generation. Inaccurate reports are made and there are often delays in finding inventory, and it is possible for errors to occur. Zahir Accounting software is a solution to solve problems that occur in this workshop. With this computerized system, financial reports can be achieved that are accurate and easy to understand compared to previously having to manually record and calculate all transactions first, the method used for this research is the method of observation, interviews and literature study.